(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2025)
Багорка Д.А. ПРАКТИЧНІ АСПЕКТИ ІНСТИТУЦІОНАЛЬНОГО РЕГУЛЮВАННЯ РОЗВИТКУ ІННОВАЦІЙНОГО БІЗНЕСУ В НАЦІОНАЛЬНІЙ ЕКОНОМІЦІ Мета. Узагальнення інституціонального інструментарію регулювання інноваційної динаміки та дослідження практичних аспектів інституціонального забезпечення розвитку інноваційного бізнесу. Методика дослідження. Теоретичною та методологічною основою дослідження виступає інституціональний підхід до обґрунтування інструментів регулювання розвитку інноваційного бізнесу в національній економіці; еволюційний підхід – до узагальнення елементів інституціонального проєктування формальних норм впливу на інноваційну динаміку; системний підхід – до обґрунтування елементів механізму формування інституціонального забезпечення розвитку інноваційного бізнесу. Результати дослідження. Констатовано, що ключовою проблемою для розвитку інноваційного бізнесу в національній економіці є його інституціональна незабезпеченість. Вона виявляється в суперечливості й архаїчності моделі інноваційного процесу, складнощах фіскального адміністрування результатів інноваційної діяльності, низькій інвестиційній активності товаровиробників та еволюційних й інституціональних обмеженнях інноваційної динаміки. Акцентовано на важливості реконструкції наявного інституціонального забезпечення інноваційного розвитку і проєктуванні проміжних інституціональних форм для сприяння розвитку інновацій в національній економіці. Аргументовано, що інституціональне конструювання здатне послабити інституціональні та еволюційні обмеження, які стримують формування ефективних інститутів. Встановлено наявність кореляції між інноваційною активністю, отриманими фінансовими результатами та домінуванням власних джерел фінансування інноваційної діяльності і впровадженням інновацій. Наукова новизна результатів дослідження. Набули подальшого розвитку теоретико-методологічні обгрунтування формування ефективного економічного інституту за допомогою визначення перспективної траєкторії його конструювання, яка виходить із ресурсних, технологічних, інституціональних обмежень та включає вбудовані механізми й інструменти, які стимулюють заплановані зміни інститутів, що, на відміну від існуючих підходів, дозволяє мінімізувати виникнення дисфункцій та інституціональних пасток. Набули подальшого розвитку пропозиції з формування оптимальних проміжних форм інституту інновацій за допомогою реалізації: моніторингу інституціонального простору (аналіз базисних, економізованих, управлінських, спеціалізованих інституцій та інститутів); оцінки інституціональних та еволюційних обмежень (ресурсів, технологій, людського капіталу, суспільних відносин, очікувань, культурного середовища, політичного впливу, комплементарності інститутів та послідовності реформ); формування сприятливих очікувань від інституціональних реформ; запровадження інструментів стимулювання інноваційного типу зростання. Практична значущість результатів дослідження. Результати проведеного дослідження можуть бути використані для проведення подальших наукових розвідок стосовно покращення інституціонального забезпечення розвитку інноваційного бізнесу Ключові слова: інноваційний бізнес, інновація, інноваційний розвиток, національна економіка, інституціональне забезпечення, інституціональний дизайн, інститут, інституція. Bahorka D.A. PRACTICAL ASPECTS OF INSTITUTIONAL REGULATION OF THE DEVELOPMENT OF INNOVATIVE BUSINESS IN THE NATIONAL ECONOMY Purpose. The aim of the article is to summarize the institutional tools for regulating innovation dynamics and to study practical aspects of institutional support for the development of innovative business. Methodology of research. The theoretical and methodological basis of the study is the institutional approach to substantiating the instruments of regulation of the development of innovative business in the national economy; the evolutionary approach is used to generalize the elements of the institutional design of formal norms of influence on innovation dynamics; system approach ‒ to substantiate the mechanism of formation of institutional support for the development of innovative business. Findings. It is stated that the key problem for the development of innovative business in the national economy is its institutional insecurity. It is manifested in the contradictions and archaic nature of the innovation process model, the difficulties of fiscal administration of the results of innovation activity, the low investment activity of commodity producers and the evolutionary and institutional limitations of innovation dynamics. Emphasis is placed on the importance of the reconstruction of the existing institutional support for innovative development and the design of intermediate institutional forms to promote the development of innovation in the national economy. It is argued that institutional design is able to weaken institutional and evolutionary constraints that restrain the formation of effective institutions. A correlation has been established between innovative activity, financial results and the dominance of own sources of financing for innovative activity and the implementation of innovations. Originality. The theoretical and methodological substantiation for the formation of an effective economic institution have been further developed by determining a promising trajectory for its construction, which proceeds from resource, technological and institutional constraints and includes built-in mechanisms and tools that stimulate planned changes in institutions, which, unlike existing approaches, allows minimizing the occurrence of dysfunctions and institutional traps. Proposals for the formation of optimal intermediate forms of the innovation institute have been further developed through the implementation of: monitoring the institutional space (analysis of basic, economized, managerial, specialized institutions and institutes); assessment of institutional and evolutionary constraints (resources, technologies, human capital, social relations, expectations, cultural environment, political influence, complementarity of institutions and sequence of reforms); formation of favourable expectations from institutional reforms; introduction of instruments to stimulate innovative growth. Practical value. The obtained results of the research can be used to conduct further scientific research on improving the institutional support for the development of innovative business. Key words: innovative business, innovation, innovative development, national economy, institutional support, institutional design, institute, institution.